2011
DOI: 10.1007/s00455-011-9338-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in Inflammatory Myopathy: Self-report, Incidence, and Prevalence

Abstract: This study compared self-reported incidence and prevalence of dysphagia in inflammatory myopathy diseases with instrumental data from videofluoroscopy in a cohort of 18 patients with inflammatory myopathies (inclusion body myositis, polymyositis, and dermatomyositis). We found a high self-report of incidence of dysphagia and demonstrated that symptoms described by the patients follow a characteristic pattern. We conclude that there is a high incidence of dysphagia in all three of the inflammatory myopathies. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 22 publications
(32 reference statements)
3
29
0
6
Order By: Relevance
“…Dysphagia in the context of inflammatory muscle diseases, such as polymyositis or dermatomyositis and cancer associated myositis [4], is frequently described, with a highly variable prevalence of 30-60% [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysphagia in the context of inflammatory muscle diseases, such as polymyositis or dermatomyositis and cancer associated myositis [4], is frequently described, with a highly variable prevalence of 30-60% [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia can sometimes be associated to several morbidities, including malnourishment, dehydration, social isolation, respiratory infections due to aspiration, and mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Paraspinal and axial muscles may be affected, resulting in head drop and camptocormia 12. Depending on the study, oropharyngeal dysphagia is reported in up to 40–86% of IBM cases, mostly due to upper esophageal sphincter dysfunction 13, 14, 15, 16. It develops insidiously, leading to frequent choking episodes and is, alongside pneumonia as a result of immobility, considered to be a potentially fatal complication of IBM.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It develops insidiously, leading to frequent choking episodes and is, alongside pneumonia as a result of immobility, considered to be a potentially fatal complication of IBM. Importantly, dysphagia may be an isolated, initial manifestation and IBM should be considered by the examining physician as differential diagnosis for new onset of dysphagia in the elderly 13, 14, 17, 18, 19, 20, 21. Early in the disease course, tendon reflexes remain unaffected, however, hyporeflexia may occur at later stages of the disease due to significant muscle atrophy 19.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Für die Dermatomyositis liegen die Häufigkeitsanga-ben bei ca. 20%, für die Polymyositis bei 30-60% und für die Einschlusskörper-chenmyositis zwischen 65 und 86% [16]. Neben neurologischen Erkrankungen spielen in diesem Kontext insbesondere auch Erkrankungen aus den Fachgebieten der Hals-Nasen-Ohren-Heilkunde, der Gastroenterologie und der Zahnheilkunde eine große Rolle.…”
Section: Primäre Und Sekundäre Presbyphagieunclassified